Pertanggungjawaban Pidana Kekerasan dengan Memaksa Orang untuk Melakukan Perbuatan Pencabulan - Ni Kadek Widya Widiani; I Made Minggu Widyantara; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2022)
Crime cases against crimes of harassment are always present in human life and attract the attention of the Sgeneral public. Crimes that are not dignified and violate the rules of norms are often used as topics in the mass media that make people worry about these cases, so that legal protection is needed for the community, especially victims related to cases of sexual harassment. The purposes of this study are to examine the regulation of criminal acts of violence by forcing people to commit acts of obscenity and criminal sanctions of violence by forcing people to commit acts of obscenity. This research is a normative legal research with a case and legislation approach. Data collection techniques were carried out by researching library materials. Legal sources are primary and secondary legal sources which are then analyzed systematically. The results of the study reveal that the regulation of criminal acts of violence by forcing people to commit acts of obscenity and criminal sanctions of violence by forcing people to commit acts of obscenity are regulated in Articles 289 to 296 of the Criminal Code.